Association between distributed leadership and teachers’ organizational commitment: Evidence from public and private schools in the United Arab Emirates - Ali Ibrahim; Shaikha Alshehhi; Nikolaos Tsingilis (PLoS ONE, 2026)
Distributed Leadership (DL) has become an important approach in contemporary school reform, promoting teacher agency, shared responsibility, and inclusive decision-making. While DL is linked to school effectiveness, its relationship with teachers’ Organizational Commitment (OC), including Affective (AC), Normative (NC), and Continuance Commitment (CC), remains underexplored, particularly in multicultural contexts such as the United Arab Emirates (UAE). This study’s main purpose was to examine how teachers’ perceptions of DL are associated with their OC in UAE schools. A quantitative, correlational design was employed with a stratified random sample of 1,040 teachers from public and private schools across all seven Emirates. Data were collected using the Distributed Leadership Scale and the TCM Employee Commitment Survey. To support the study objective, measurement analyses were conducted to clarify the structure of the scales. Confirmatory Factor Analysis indicated that a bifactor model provided the best representation of OC across the examined models. Based on consistent empirical results across subsamples and conceptual considerations, two weak CC items were removed, resulting in a more coherent operationalization of the construct. Demographic variables were also examined as contextual factors that may shape the relationship between DL and OC. The findings showed that DL was widely perceived across schools, with public schools reporting slightly higher levels. Structural Equation Modeling indicated a strong positive association between DL and overall OC, particularly for affective and normative commitment, while the association with continuance commitment was weaker. School type showed a limited association with commitment, indicating that DL is more strongly related to teachers’ OC than school type. Demographic variations emerged for nationality, qualifications, experience, school cycle, and school location, but not for gender. The study provides theoretical and practical insights into how DL is associated with teachers’ OC in culturally diverse educational systems and contributes to international literature by supporting the use of these instruments in non-Western settings.